Midian - A Land or a League? - Dumbrell, W. J.
‛Êpāh son of Midian identified with ḫa-a-pa-a-a (ḫa-a-a-pa-a) of annals of Tigl. III and Sar. II; um-ma-at tur/már-mi-im ‘perfidious confederation (?)’, Yaḫdun-Lim.